A post-colonial political theology of care and praxis in Ethiopia’s era of identity politics - N.A. Terefe (Acta Theologica)
This book is a revised version of the author’s PhD thesis that was submitted to Denver University and the Iliff School of Theology. In the introductory section, the author discusses how her social location motivated her to research the topic of identity politics in Ethiopia. She argues that identity politics has been a major factor in Ethiopia’s political instability and violence. Ethiopia experiences frequent identity-based violence. Molla indicates that identity politics has divided Ethiopian society and eliminated in-between spaces where people can coexist in equality, solidarity, and justice. She proposes a post-colonial political theology of care and practice to reframe hegemonic and fragmented identities and create new in-between spaces for dialogue and cooperation. She contends that post-colonial discourse and the praxis of in between pastoral care can disrupt and challenge hegemonic definitions of culture, identity, home, and subjectivity.